Navigating Halal Tourism: Perceptions and Behaviors of Non-Muslims in the Muslim-Minority Context of Manado City - Djamali, Radjab; Kindangen, Paulus; Masinambow, Vecky A. J.; Taroreh, Rita N.; Nurhayati, Laily; Hermawan, Tulus (IAIN Manado, 2025)
This study aims to examine the perceptions and behaviors of the non-Muslim community in Manado towards halal tourism, particularly in the context of a Muslim-minority region. As halal tourism gains momentum, driven by Muslim travelers seeking destinations that align with Islamic principles, it becomes crucial to understand how this tourism concept is perceived in areas with predominantly non-Muslim populations. Using a qualitative approach with a descriptive methodology, data were gathered through in-depth interviews and observations, followed by analysis based on Miles and Huberman's interactive model. The findings reveal diverse perceptions of halal tourism among non-Muslim residents of Manado. While most participants associate halal tourism with halal food and an environment adhering to Islamic principles, others interpret it more broadly, relating it to cleanliness, orderliness, and respect for social and cultural diversity norms. Despite these varying perspectives, most participants favor developing Manado as a halal tourism destination. These findings provide valuable insights into the integration of halal tourism in non-Muslim-majority contexts, offering implications for policy development and the future of halal tourism in Indonesia.